OUT OF SIGHT, STILL IN MIND: visually impaired women's embodied accounts of ideal femininity - Fannon, Tara A. (Disability Studies Quarterly, 2016)
<!-- P { margin-bottom: 0.08in; direction: ltr; color: rgb(0, 0, 10); }P.western { font-family: "Times New Roman",serif; font-size: 12pt; }P.cjk { font-family: "Arial Unicode MS",sans-serif; font-size: 12pt; }P.ctl { font-family: "Arial Unicode MS",sans-serif; font-size: 12pt; }A:link { } --> With its emphasis on physical form, the diffusion of the feminine ideal relies heavily on the use of visual imagery but there is a common knowledge about the feminine ideal that penetrates language and discourse. The relationship between mainstream representations of the feminine ideal and non-disabled female body/self dissatisfaction has been well-documented over the years but less attention has been given to understanding how such visual representations affect women with disabilities, specifically women with visual disabilities. Drawing on qualitative data taken from the personal diaries and in-depth interviews with seven blind and visually impaired Irish women, and using a feminist disability model reinforced by sociology of the body, gender theory and visual studies, I examine what it means to be a young woman with a visual disability living in a visually-reliant, appearance-oriented culture. I explore interpretations and expressions of femininity and beauty, the complicated, often fraught, relationship with female body and self and the rituals and practices used to manage appearance while having a disability.